2019
DOI: 10.1108/jeim-09-2018-0197
|View full text |Cite
|
Sign up to set email alerts
|

How does business-IT strategic alignment dimension impact on organizational performance measures

Abstract: Purpose Despite the conceptual, empirical and theoretical advances in alignment–performance relationship, there is a limited research on the alignment dimensions and organizational performance measures. Though strategic alignment is believed to improve organizational performance, the purpose of this paper is to develop conjectures for understanding how different alignment dimensions influence organizational performance measures. Design/methodology/approach The data were acquired from 161 senior IT and busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 66 publications
3
63
0
6
Order By: Relevance
“…Adopting a new technology is only vital if it really improves the performance of business organisations (Yunis, Tarhini, and Kassar, 2018). Effectively adopting and aligning an IT resource to enhance the organisational core competencies boosts firm performance (Ilmudeen, Bao, and Alharbi, 2019). The study of Gupta, Qian et al (2018) showed that both cloud ERP and big data had a positive and significant impact on operational and market performance.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Adopting a new technology is only vital if it really improves the performance of business organisations (Yunis, Tarhini, and Kassar, 2018). Effectively adopting and aligning an IT resource to enhance the organisational core competencies boosts firm performance (Ilmudeen, Bao, and Alharbi, 2019). The study of Gupta, Qian et al (2018) showed that both cloud ERP and big data had a positive and significant impact on operational and market performance.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Eichhorn and Towers (2015) agree that the support of the CEO is key in the execution of the alignment and construction of goals and incentives, so that they integrate and motivate their talent. Regarding the mediation of the alignment of the data plan with the business plan, the literature establishes that managers must pay attention to it and develop more complete action plans to achieve a better strategic business-IT alignment, as well as translate the alignment into superior effects of IT on company performance (Aboobucker et al, 2019). One of the main advantages that senior managers can discuss with their subordinates, the planning of their IT projects, is that all corporate divisions improve strategic alignment (Peak & Guynes, 2003).…”
Section: Groupmentioning
confidence: 99%
“…Al Nahyan et al, 2019;Ilmudeen et al, 2019;McNurlin et al, 2009;Pai, 2006;Park and Kim, 2018;Preston and Karahanna, 2009;Piccoli, 2008;Yeh et al, 2011 Consideration of internal and external environment (CIEE)…”
Section: Sisp Facilitatorsmentioning
confidence: 99%
“…Argote, 2005;Bhatt and Grover, 2005;Hovelja et al, 2010;Otim et al, 2009;Park and Kim, 2018;Peppard and Ward, 2004;Reponen, 1998 The extent to which the mission, objectives, and plans contained in the business strategy are closely linked, shared, and supported by the IT mission, objectives, and plans. Chan, 2002;Earl, 1993;Ilmudeen et al, 2019;Kitsios and Kamariotou, 2019b;Maharaj and Brown, 2015;Őri, 2018;Reich andBenbasat, 1996, 2000;Teo, 2009 The impact of SISP success Organisational capabilities (Orcap)…”
Section: Sisp Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation